A Rare Presentation of Orbital Castleman’s Disease - Ruchi Goel; Akash Raut; Ayushi Agarwal; Shweta Raghav; Sumit Kumar; Simmy Chaudhary; Priyanka Golhait; Sushil Kumar; Ravindra Saran (Case Reports in Ophthalmological Medicine)
Castleman’s disease (CD) is an uncommon group of atypical lymphoproliferative disorders. Extranodal involvement such as the orbit is extremely rare. We aim to report a case of a 62-year-old male who presented with left painless proptosis for the past three years. Examination revealed a firm, lobulated mass in the left superotemporal orbit, displacing the globe inferomedially. A well-defined extraconal orbital lesion encasing the left lateral rectus muscle with intraconal extension was seen on Magnetic Resonance Imaging (MRI) that led to the provisional diagnosis of left solitary encapsulated venous malformation. Excision of the mass via lateral orbitotomy was performed. However, on histopathology, the features were consistent with a mixed-cell variant of Castleman’s disease. A detailed systemic workup was unremarkable. Proptosis resolved after surgery and no recurrence was noted in the three-year follow-up. To the best of our knowledge, this is the first case report of a mixed-cell variant of unicentric orbital CD without any systemic features. This case highlights the importance of including CD in the differential diagnosis of well-defined orbital lesions so as to enable its early detection and timely management.